Large Overlap Between the Intestinal and Reproductive Tract Microbiomes of Chickens - Shterzer, Naama; Rothschild, Nir; Sbehat, Yara; Stern, Einav; Nazarov, Albert; Mills, Erez (Frontiers in Microbiology, 2020)
Recent work characterized the chicken reproductive tract (oviduct) microbiome composition and its similarity to the egg and chick microbiomes. However, the origin of the oviduct microbiome has not been addressed yet. Here we characterized the microbiome composition along the oviduct (infundibulum, magnum and shell gland) as well as in the gut (jejunum and cecum) of broiler breeders at 37 weeks of age of the Cobb industrial breed. We found that while the microbiome composition along the oviduct is similar, the three sites, jejunum, cecum and oviduct hold distinct microbiomes. However, there was also a large overlap in the composition of the gut and oviduct microbiomes, with 55% and 53% of amplicon sequence variants (ASVs) representing 96% and 90% of the total abundance in the jejunum and cecum, respectively, shared with the magnum. Furthermore, we identified a strong correlation between the relative abundance of ASVs in the gut and their probability to be found in the oviduct. These results suggest that material from the gut travels the full length of the oviduct. This is possibly the result of chicken physiology which includes the cloaca, a cavity to which both the intestinal and reproductive tract open into. As the cloaca is common to birds, reptiles, amphibians, most fish, and monotremes, our finding may be relevant to many vertebrates. Importantly, these results indicate that mere presence in, and ascending of the oviduct are not virulence characteristics specific to pathogens, as commonly thought, but are the result of chicken physiology and characterize all gut bacteria. Furthermore, whereas a vertical transmission route from the hen to the chick has been suggested, our work starts laying a mechanistic foundation to this route, by describing the movement of gut bacteria to the oviduct, where they may be enclosed in the developing egg. Last, as our results show that gut material travels the full length of the oviduct, fertilization in poultry occurs in the presence of at least bacterial products if not live bacteria, and therefore food additives, probiotics and diet possibly have a much more direct effect on reproduction and egg formation than previously considered.